Acidic electrolyzed water treatment suppresses Phomopsis longanae Chi-induced the decreased storability and quality properties of fresh longans through modulating energy metabolism. (15th March 2023) - Li, Meiling; Lin, Qin; Chen, Yazhen; Chen, Yihui; Lin, Mengshi; Hung, Yen-Con; Lin, Hetong
Highlights: AEW treatment suppressed P. longanae -induced disease occurrence of fresh longan. AEW treatment led to higher energy status and ATPase activities in inoculated longan. AEW treatment maintained the storability and quality properties of inoculated longans. AEW treatment extended the storage-life of longan by regulating energy metabolism. Abstract: Longan fruit loses its market value rapidly due to postharvest pathogenic infestation and quality deterioration. Here, we hypothesized that acidic electrolyzed water (AEW) could maintain higher quality of P. longanae -inoculated longans via regulating energy metabolism. Results indicated that AEW reduced fruit disease index and decay incidence. Significantly, AEW treatment retained higher levels of ATP, ADP, and energy charge, and higher activities of Ca 2+ -ATPase, Mg 2+ -ATPase, and H + -ATPase in the membranes of plasma, vacuole, and mitochondria, which maintained the structural and functional integrity of cell membrane. Furthermore, indirectly sustaining cell membrane function via AEW treatment could maintain the storability and quality properties of longans, including keeping higher values of color chromaticity ( L *, a *, and b *), higher amounts of vitamin C, total soluble solids, sucrose, and total soluble sugars, lower titratable acid and reducing sugar contents. This work elucidated the potential regulation of AEW on the balance of energy metabolism and fruit quality.